Donor Preference Meets Heterochromatin: Moonlighting Activities of a Recombinational Enhancer in Saccharomyces cerevisiae - Dodson, Anne E; Rine, Jasper (Genetics (Austin), 2016)
In Saccharomyces cerevisiae, a small, intergenic region known as the recombination enhancer regulates donor selection during mating-type switching and also helps shape the conformation of chromosome III. Using an assay that detects transient losses of heterochromatic repression, we found that the recombination enhancer also acts at a distance in cis to modify the stability of gene silencing. In a mating-type-specific manner, the recombination enhancer destabilized the heterochromatic repression of a gene located ∼17 kbp away. This effect depended on a subregion of the recombination enhancer that is largely sufficient to determine donor preference. Therefore, this subregion affects both recombination and transcription from a distance. These observations identify a rare example of long-range transcriptional regulation in yeast and raise the question of whether other cis elements also mediate dual effects on recombination and gene expression.